2020
DOI: 10.1155/2020/3751827
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Outcomes of Elective-Start versus Urgent-Start Peritoneal Dialysis Catheter Placement

Abstract: The aim of this study is to compare the outcomes of the elective-start versus urgent-start use of peritoneal dialysis (PD) catheters using percutaneous radiologic or laparoscopic techniques. Patients having their first peritoneal dialysis catheter placed and used between January 2005 and January 2018 were identified, and their medical records were retrospectively reviewed. Two groups were identified: elective-start (n = 211) and urgent-start (n = 29). Patient’s demographics were similar between the two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“… 15 Compared with elective-start PD, urgent-start PD had lower rates of catheter dysfunction (i.e., 17.2% vs. 28.4%) yet higher rates of catheter leakage (13.8% vs. 3.3%). 16 The high number of leaks in this study could be associated with the short catheter break-in time. The time to catheter opening has also been proven to affect the frequency of complications.…”
Section: Discussionmentioning
confidence: 74%
“… 15 Compared with elective-start PD, urgent-start PD had lower rates of catheter dysfunction (i.e., 17.2% vs. 28.4%) yet higher rates of catheter leakage (13.8% vs. 3.3%). 16 The high number of leaks in this study could be associated with the short catheter break-in time. The time to catheter opening has also been proven to affect the frequency of complications.…”
Section: Discussionmentioning
confidence: 74%
“…2 36 37 38 It also allows for urgent initiation of PD and avoidance of temporary vascular access catheters in late-referred ESRD patients, without significant increase in the complication rate in comparison to elective-start PD. 2 39 In a meta-analysis of 13 studies with a total of 2,681 patients, Boujelbane et al found no significant difference in catheter survival between percutaneous and surgical placement of PD catheters. 40 Furthermore, Abdel Aal et al found similar survival and complication rates between fluoroscopically inserted PD catheters and those which were inserted laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…14 Also, early use of PD (break-in period of fewer than 7 days) was associated with catheter dysfunction and peritonitis 7 and, in another study, with an increased rate of leaks. 15 Other cohort studies corroborate that the first year of PD therapy is a period with high morbidity, especially in the first months of this treatment. 16…”
Section: Introductionmentioning
confidence: 79%